Highly sensitive flexible strain sensor based on carbon nanotube/styrene butadiene styrene@ thermoplastic polyurethane fiber with a double percolated structure. Issue 1 (12th November 2022) - Liu, Libing; Xiang, Dong; Zhang, Xiangxia; Harkin‐Jones, Eileen; Wang, Junjie; Zhao, Chunxia; Li, Hui; Li, Zhenyu; Wang, Li; Wang, Ping; Li, Yuntao; Wu, Yuanpeng
Abstract: The combination of a high sensitivity and a wide strain detection range in conductive polymer composites‐based flexible strain sensors is still challenging to achieve. Herein, a double‐percolation structural fiber strain sensor based on carbon nanotubes (CNT)/styrene butadiene styrene (SBS)@thermoplastic polyurethane (TPU) composite was fabricated by a simple melt mixing and fused filament fabrication strategy, in which the CNT/SBS and TPU were the conductive and insulating phases, respectively. Compared with the sensor without the double percolated structure, the CNT/SBS@TPU sensor achieved a lower percolation threshold (from 2.0 to 0.5 wt%, a reduction of 75%), and better electrical and sensing performance. It is shown that the strain detection range of the CNT/SBS@TPU sensor increases with increasing CNT loading. An opposite trend was observed for the sensitivity. The 1%‐CNT/SBS@TPU sensor exhibited a high conductivity (1.08 × 10 −3  S/m), high sensitivity (gauge factor of 2.65 × 10 6 at 92% strain), wide strain detection range (0.2%–92% strain), high degree of linearity ( R 2  = 0.954 at 0–10% strain), broad monitoring frequencies (0.05–0.5 Hz), and excellent stability (2000 cycles). Moreover, the CNT/SBS@TPU sensor was shown to successfully monitor a range of human physiological activities and to be capable of tactile perception and weight distribution sensing. Abstract : A highly sensitive fiber flexible strain sensor with a double percolated structure.